2013
DOI: 10.1093/molehr/gat012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in TGFB1 gene and risk of idiopathic recurrent pregnancy loss

Abstract: Transforming growth factor β1 plays a significant role in pregnancy outcome. We investigated the association of TGFB1 exon 1 (rs1800471, rs1800470) and promoter region (rs1800469, rs1800468) polymorphisms with recurrent pregnancy loss (RPL) in 675 Tunisian women: 304 women with a history of three consecutive pregnancy losses of unknown etiology with the same partner and 371 age-matched multiparous control women. TGFB1 genotyping was done by TaqMan assays. Higher minor allele frequency for rs1800471 (P< 0.001),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 38 publications
3
12
1
Order By: Relevance
“…However, a plausible line of reasoning could be that the intermediary circulating levels of TGF-b1 generated as a consequence of joint action of the two heterozygous genotypes might help in proper angiogenesis and immunomodulation required for the maintenance of normal pregnancy. We detected strong linkage disequilibrium between the TGFB1 C-509T and T869C polymorphisms in concurrence with former reports allowing us to analyse the influence of the four different haplotypes on PE, which might possibly be more informative than single SNP analysis [46]. The emergence of haplotypes T-T and C-C as significantly high-risk combinations could be explained based on a possible interaction between the two polymorphisms which are both functional variants; the promoter polymorphism affecting the expression and the exonic variant influencing the secretion of mature TGF-b1 might in someway result in altered plasma levels of TGF-b1 and cause either constitutively high/low amounts of this cytokine.…”
Section: Discussionsupporting
confidence: 90%
“…However, a plausible line of reasoning could be that the intermediary circulating levels of TGF-b1 generated as a consequence of joint action of the two heterozygous genotypes might help in proper angiogenesis and immunomodulation required for the maintenance of normal pregnancy. We detected strong linkage disequilibrium between the TGFB1 C-509T and T869C polymorphisms in concurrence with former reports allowing us to analyse the influence of the four different haplotypes on PE, which might possibly be more informative than single SNP analysis [46]. The emergence of haplotypes T-T and C-C as significantly high-risk combinations could be explained based on a possible interaction between the two polymorphisms which are both functional variants; the promoter polymorphism affecting the expression and the exonic variant influencing the secretion of mature TGF-b1 might in someway result in altered plasma levels of TGF-b1 and cause either constitutively high/low amounts of this cytokine.…”
Section: Discussionsupporting
confidence: 90%
“…The increased TGFβ1 bioavailability due to increased TGFβ1 and decreased levels of its receptor may contribute to PCOS pathogenesis and ovarian hyperstimulation [60,62]. Several TGFβ1 gene polymorphisms have been reported; some have been shown to have an important correlation with TGFβ1 production and disease severity in studies involving the association between TGFβ1 polymorphisms and RSA [63]. The current study has shown no significant allele or genotype associations of TGFβ1-509T/C in RSA patients with or without PCOS confirming data previously published [63,64].…”
Section: Discussionsupporting
confidence: 89%
“…It has been described that JAK–STAT5 signaling pathway has a key function in preimplantation embryo development, always susceptible to RM [ 41 ]. The previous study proved that a TGF-β1 level was increased in maternal plasma during pregnancy, but decrease rapidly later birth [ 42 , 43 ]. It has been reported that TGF-β1 level was increased in three out of eight nonpregnant women with a past history RM [ 42 ].…”
Section: Discussionmentioning
confidence: 99%